2003
DOI: 10.1074/jbc.m309034200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Processing of CD4 T-cell Epitopes from the Protective Antigen of Bacillus anthracis

Abstract: We have mapped CD4؉ T-cell epitopes located in three domains of the recombinant protective antigen of Bacillus anthracis. Mouse T-cell hybridomas specific for these epitopes were generated to study the mechanisms of proteolytic processing of recombinant protective antigen for antigen presentation by bone marrow-derived macrophages. Overall, epitopes differed considerably in their processing requirements. In particular, the kinetics of presentation, ranging from 15 (fast) to 120 min (slow), suggested sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 60 publications
(48 reference statements)
1
28
0
Order By: Relevance
“…Those results are confirmed here, since antibodies could be generated against PA30 (amino acids 671 to 700 of PA) when it was inserted into HVR5. However, in studies that defined CD4 ϩ T-cell epitopes of PA, no T-cell epitopes were found encompassing residues 671 to 700 (40). We thus sought to characterize the T-cell response to PA30 in the context of HVR5 to determine if it was able to be processed such that it could activate cellular immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Those results are confirmed here, since antibodies could be generated against PA30 (amino acids 671 to 700 of PA) when it was inserted into HVR5. However, in studies that defined CD4 ϩ T-cell epitopes of PA, no T-cell epitopes were found encompassing residues 671 to 700 (40). We thus sought to characterize the T-cell response to PA30 in the context of HVR5 to determine if it was able to be processed such that it could activate cellular immunity.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that impaired AM proteolysis affects antigen processing and presentation (21), resulting in suboptimal initiation of antigen-specific alveolar CD4 1 T-cell responses. Impaired AM innate immune functions may, therefore, leave HIV-infected individual on ART vulnerable to LRTI.…”
Section: Discussionmentioning
confidence: 99%
“…However, few candidate vaccine antigens have been sub-jected to a detailed study of the mechanisms of antigen presentation of multiple epitopes (34,35). We investigated antigen presentation of rCaf1 to helper T cells and observed major differences between epitopes depending on their location within the recently solved Caf1 structure (10).…”
mentioning
confidence: 99%